Collective Leadership Dynamics among Professional Peers: Co-constructing an unstable equilibrium. Issue 9 (September 2020) - Empson, Laura; Alvehus, Johan
Professional service firms (PSFs) are characterized by contingent and contested power relations among an extended group of professional peers. Studies of such firms can therefore yield important insights for the literatures on collective leadership and leader–follower relations. Yet to date PSF scholars have neglected the topic of leadership, and leadership scholars have neglected the context of PSFs. Based on 102 interviews across the consulting, accounting and legal sectors, we identify three relational processes through which professional peers co-construct collective leadership: legitimizing, negotiating and manoeuvring. We demonstrate how the relational processes taken together constitute an unstable equilibrium, both in the moment and over time, emphasizing how leadership in PSFs is inherently contested and fragile. Our model contributes to theories of collective leadership and leader–follower relations by foregrounding the power and politics that underlie collective leadership. We highlight the significance of the individual leader within the collective. We challenge assumptions concerning the binary nature of leadership and followership, by showing how colleagues may grant leadership identities to their peers without necessarily granting them leadership authority, and without claiming follower identities for themselves.